If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -18 = 3x + 9 Reorder the terms: -18 + 4x = 3x + 9 Reorder the terms: -18 + 4x = 9 + 3x Solving -18 + 4x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -18 + 4x + -3x = 9 + 3x + -3x Combine like terms: 4x + -3x = 1x -18 + 1x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -18 + 1x = 9 + 0 -18 + 1x = 9 Add '18' to each side of the equation. -18 + 18 + 1x = 9 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = 9 + 18 1x = 9 + 18 Combine like terms: 9 + 18 = 27 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| 7x+21=91 | | 116-31=x | | 5x+0.5y+1z=100 | | 3/35-8 | | 35/3-8 | | 3(9-6x)-10x=1 | | 12(y+89)= | | 10x-118=2x-6 | | 75+75=x | | 4u-7=-35 | | 6-x^2=-39 | | 124+37=x | | 27x^7/9x^2 | | x+(12)=8 | | 60+63=x | | n*1270=375 | | 4x-13=5x+8 | | 40+(5x+14)=x | | 9j+12k-3p=0 | | y^-9/y^-6 | | -2t^3+12t^2+32t=0 | | x+252=3x | | 24n=13m+19 | | 4(9+3x)-12=16 | | 6(4x+2)+3(2x+3)+5=30x+27 | | 5X-2X+7=X+2 | | F(x)=4-5y | | 1622/180 | | f(n)=2.5+3(n-1) | | 1620/180 | | p*2.90=2.1 | | 4XY=80.8 |